Effect of Post Clinical Debriefing in Enhancing Clinical Decision Making Ability among Diploma Nursing Students: A Mixed Methods Study - Than, Soo Nyet (2015)
This study aimed to examine the effect of using post clinical debriefing as an educational intervention in enhancing the clinical decision making ability among diploma nursing students. This was because making improvement in nursing students’ clinical decision making skills has been a difficult academic outcome to achieve, despite considerable research and a major focus topic for nursing education. A mixed methods study using triangulation design was used. Analogy-guided learning and guided reflection were included in post clinical debriefing as treatment. Quantitative method using quasi-experimental study with pre-test & post-test was conducted among 133 Second Year Semester One Diploma Nursing students (experimental n=64; control n=69) in a public university. Two instruments were used to measure their context specific and general clinical decision making skills and a satisfaction questionnaire was used to obtain their perception of the treatment. Qualitative method used focus group interviews to explore any factors that might have effect on their clinical decision making. Significant difference in the intervention group was found in the dimensions of “hypothesis generation” and “cue utilisation” within the framework of the nursing process which supported the hypotheteco-deductive diagnostic reasoning theory. Supportive clinical environments and multiple patients experience were factors found to enhance students’ diagnostic reasoning skills. A Model of Factors Enhancing Clinical Decision Making for Diploma Nursing Students was synthesized based on the data of this study as a guide for future educational intervention.